Studies in Economic Theory
DOI: 10.1007/3-540-29500-3_10
|View full text |Cite
|
Sign up to set email alerts
|

Money, price dispersion and welfare

Abstract: Summary.We introduce heterogeneous preferences into a tractable model of monetary search to generate price dispersion, and then examine the effects of money growth on price dispersion and welfare. With buyers' search intensity fixed, we find that money growth increases the range of (real) prices and lowers welfare as agents shift more of their consumption to less desirable goods. When buyers' search intensity is endogenous, multiple equilibria are possible. In the equilibrium with the highest welfare level, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
1

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 18 publications
1
13
0
1
Order By: Relevance
“…Lemma 2 For any givenẑ z, the optimal solution (q e ; z e ; v e ) for all e 2 [0; 1] to the seller's price-posting problem is unique and is characterized by 1 1 Exceptions are Peterson and Shi (2004) and Faig and Jerez (2006). Both papers feature buyers having private information about match speci…c preference shocks.…”
Section: Seller' S Price Posting Decisionmentioning
confidence: 99%
“…Lemma 2 For any givenẑ z, the optimal solution (q e ; z e ; v e ) for all e 2 [0; 1] to the seller's price-posting problem is unique and is characterized by 1 1 Exceptions are Peterson and Shi (2004) and Faig and Jerez (2006). Both papers feature buyers having private information about match speci…c preference shocks.…”
Section: Seller' S Price Posting Decisionmentioning
confidence: 99%
“…Counter to the intuition held by Fisher and many others, in such a model, increases in inflation do not increase the willingness to trade of agents holding money. This result is highlighted by Lagos and Rocheteau (2005), who showed that in an extended Lagos-Wright framework including a search intensity decision, when inflation increases, agents tend to reduce their effort to engage in (monetary) transactions (see also Peterson and Shi, 2004). In other words, agents do not search more and/or try to spend their money speedily in response to inflation.…”
Section: Introductionmentioning
confidence: 96%
“…In the monetary search models (Peterson and Shi, 2004;Head and Kumar, 2005), the effect of inflation on price dispersion works through the channel of consumers' search costs. On the one hand, higher expected inflation reduces the real value of fiat money and raises consumers' reservation price levels; this increases firms' market power and, consequently, price dispersion.…”
mentioning
confidence: 99%